(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the musical and genre features of kyu as a phenomenon of Kyrgyz traditional music. Particular attention is paid to understanding kyuu as a phenomenon, its formation, historical, aesthetic and spiritual significance in the context of Kyrgyz culture. The author considers kyuu not only as a musical genre, but also as an expression of national artistic thinking. It also analyzes kyu as a special artistic form that reflects the worldview of the people, historical memory and spiritual values in the context of traditional Kyrgyz culture. The structure of kyuu, methods of performance, emotional and expressive features and its place in the folklore space are explored. Also covered are the genre varieties of kyuu, performance traditions and the process of passing on musical heritage from generation to generation.